1 H MRS: a potential biomarker of in utero placental function. (27th August 2015) - Macnaught, Gillian; Gray, Calum; Walker, Jane; Simpson, Mary; Norman, Jane; Semple, Scott; Denison, Fiona
<x xml:space="preserve">Abstract</x> The placenta is a temporary organ that is essential for a healthy pregnancy. It performs several important functions, including the transport of nutrients, the removal of waste products and the metabolism of certain substances. Placental disorders have been found to account for over 50% of stillbirths. Despite this, there are currently no methods available to directly and non‐invasively assess placental function in utero. The primary aim of this pilot study was to investigate the use of 1H MRS for this purpose. 1H MRS offers the possibility to detect several placental metabolites, including choline, lipids and the amino acids glutamine and glutamate (Glx), which are vital to fetal development and placental function. Here, in utero placental spectra were acquired from nine small for gestational age (SGA) pregnancies, a cohort who are at increased risk of perinatal morbidity and mortality, and from nine healthy gestation‐matched pregnancies. All subjects were between 26 and 39 weeks of gestation. Placenta Glx, choline and lipids at 1.3 and 0.9 ppm were quantified as amplitude ratios to that of intrinsic H2O. Wilcoxon signed rank tests indicated a significant difference in Glx/H2O (p = 0.024) between the two groups, but not in choline/H2O (p = 0.722) or in either lipid/H2O ratio (1.3 ppm, p = 0.813; 0.9 ppm, p = 0.058). This study has demonstrated that 1H MRS has potential for the detection of placental metabolites in utero. This warrants further investigation as a tool for the monitoring of placental function. Copyright © 2015 John Wiley & Sons, Ltd.